Learning path : scrum practitioner. - Norman, Tommy; Safari eBooks ([Place of publication not identified] : Addison-Wesley, 2016)
"Scrum Fundamentals LiveLessons provides practitioners with a core understanding of Scrum(13)the most popular agile method(13)and helpful advice to help them deliver high quality products that add the most value to their customers. In this video training, Tommy Norman (CSM, CSP, PSM I, ALM MVP) provides an introduction to Agile software development using Scrum, which is a lightweight, adaptive framework for managing complex projects. It consists of roles, artifacts, and events as well as a simple set of rules to govern the relationships and interactions between them. This LiveLessons course gives helpful insight into the history of Agile and how its values and principles can focus teams on consistently delivering quality products that immediately add value for the customer. It covers the complete Scrum framework from project initiation, executing Sprints, and delivering a product increment."--Resource description page.
Scrum fundamentals and advanced / Tommy Norman -- Advanced scrum / Tommy Norman -- Lean principles for scrum : LiveLessons / Tommy Norman.
Presenters, Tommy Norman
Title and publication information from resource description page (Safari, viewed September 21, 2016).
Keywords: Scrum (Computer software development); Application software -- Development; Web applications -- Design; Electronic books